Characterization of nanofibrillated cellulose produced from Oil Palm Empty Fruit Bunch Fibers (OPEFB) using ultrasound. - Ramli Rosazley, M.Z Shazana, M.A. Izzati, A.W. Fareezal, I. Rushdan, Z.M.A. Ainun (Universiti Pendidikan Sultan Idris, 2016)
Characterization of nanofibrillated cellulose produced from Oil Palm Empty Fruit Bunch Fibers (OPEFB) using ultrasound. by Ramli Rosazley, M.Z Shazana, M.A. Izzati, A.W. Fareezal, I. Rushdan, Z.M.A. Ainun,